Sahara : A Novel - Cussler, Clive (London HarperCollins Publishers, 1993)
The eleventh classic Dirk Pitt novel, where the adventurer is drawn to a secret in the burning African desert, which could destroy all life in the world's seas.
English Fiction.
Keywords: Pitt, Dirk (Fictitious character) -- Pollution -- Sahara